Circadian Rhythm Disturbances Due to Exposure to Acidified Conditions and Different Photoperiods in Juvenile Olive Flounder (Paralichthys olivaceus) - Lee, Dae-Won; Song, Jin Ah; Park, Heung-Sik; Choi, Cheol Young (Ocean science journal, 2021)
Carbon dioxide (CO 2 ) is being continuously discharged into the atmosphere and is now at a concentration sufficient to cause ocean acidification. In particular, it has been reported that changes in carbonate concentration in seawater by ocean acidification can inhibit olfactory function and predator avoidance ability in fish and affect their circadian rhythm. However, although increased CO 2 concentration in seawater is an important environmental factor affecting fish survival, only a few studies have been conducted to evaluate the effect of CO 2 and different photoperiods. Therefore, in this study, we investigated changes in the circadian rhythm of juvenile olive flounder ( Paralichthys olivaceus ) under different light conditions (12 h ligh:12 h dark; constant dark; constant light) and CO 2 exposure levels (pH 8.1, 7.8, and 7.5), by analyzing changes in plasma concentrations of Cryptochrome1 and Period2, which are secreted during the day (light conditions), and melatonin, which is secreted at night (dark conditions). CO 2 exposure led to phase shifts (temporarily abolished, phase delayed, or reversed) in the rhythm of juveniles. In conclusion, CO 2 exposure, along with changes in photoperiods, increases the disturbance in the circadian rhythm of juvenile P. olivaceus .